Exploration of Social Risk Factors in cases of Stunting in Children Aged 1-5 Years in Ngesrep sub-district, Semarang City - nisa aisyah; Nabila Nurul Hawa (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Stunting in toddlers is not merely a medical issue but also a public health challenge in Indonesia, including urban areas such as Semarang City. This study aims to analyze social risk factors that play an important role in the occurrence of stunting among children aged 1–5 years in Kelurahan Ngesrep, Semarang City. The study employed a descriptive qualitative method with data collection techniques including in-depth interviews and direct observations involving mothers of stunted children, posyandu cadres and the village social welfare section (social welfare). The findings indicate that most stunted children come from families with relatively low maternal education levels, predominantly high school graduates. This level of education influences parents’ understanding in applying appropriate child-rearing practices. In addition to educational factors, parents’ time and attention toward their children are limited due to work-related demands. This condition affects the quality of parenting and social support within the surrounding environment. Work obligations also prevent some mothers from regularly attending posyandu activities, resulting in suboptimal monitoring of children’s growth and development.Based on these findings, it can be concluded that stunting is a multidimensional problem involving maternal education, parenting practices, and community social support. This study is expected to provide insights for the government and health professionals in designing more effective and efficient stunting prevention programs in urban areas.